Odpowiedź :
Odpowiedź:
a)
3(2 - 3x) = x - 4
6 - 9x = x - 4
- 9x - x = - 4 - 6
- 10x = - 10
10x = 10
x = 10/10 = 1
b)
5x - 7 = 0 * (x + 11) - 2(1 - 3x)
5x - 7 = - 2 + 6x
5x - 6x = - 2 + 7
- x = 5
x = - 5
c)
2(x - 1) + x = x - 3(2- 3x)
2x - 2 + x = x - 6 + 9x
3x - 2 = 8x - 6
3x - 8x = - 6 + 2
- 5x = - 4
5x = 4
x = 4/5
d)
2x + 15 ≥ 6x + 7
2x - 6x ≥ 7 - 15
- 4x ≥ - 8
4x ≤ 8
x ≤ 8/4
x ≤ 2
x ∈ (- ∞ , 2 >
e)
5x+ 2 < 7x + 6
5x - 7x < 6 - 2
- 2x < 4
2x > - 4
x > - 4/2
x > - 2
x ∈ ( - 2 , + ∞ )
f)
x + 1 ≥ 2x + 3
x - 2x ≥ 3 - 1
- x ≥ 2
x ≤ - 2
x ∈ (- ∞ , - 2 >
Odpowiedź:
[tex]a)\\\\3(2-3x)=x-4\\\\6-9x=x-4\\\\-9x-x=-4-6\\\\-10x=-10\ \ /:(-10)\\\\x=1\\\\\\b)\\\\5x-7=0(x+11)-2(1-3x)\\\\5x-7=0-2+6x\\\\5x-7=-2+6x\\\\5x-6x=-2+7\\\\-x=5\ \ /\cdot(-1)\\\\x=-5\\\\\\c)\\\\2(x-1)+x=x-3(2-3x)\\\\2x-2+x=x-6+9x\\\\3x-2=10x-6\\\\3x-10x=-6+2\\\\-7x=-4\ \ /:(-7)\\\\x=\frac{4}{7}[/tex]
[tex]d)\\\\2x+15\geq 6x+7\\\\2x-6x\geq 7-15\\\\-4x\geq -8\ \ /:(-4)\\\\x\leq 2\\\\x\in(-\infty,2\rangle\\\\\\e)\\\\5x+2<7x+6\\\\5x-7x<6-2\\\\-2x<4\ \ /:(-2)\\\\x>-2\\\\x\in(-2,+\infty)\\\\\\f)\\\\x+1\geq 2x+3\\\\x-2x\geq 3-1\\\\-x\geq 2\ \ /\cdot(-1)\\\\x\leq -2\\\\x\in(-\infty,-2\rangle[/tex]